Power, community and the state : the political anthropology of organisation in Mexico - Nuijten, Monique (Pluto Press, 2003)
Annotation This book explores the balance of power between the state and local communities, with particular reference to societies in the developing world. Nuijten shows how rituals of bureaucratic power and accusations of corruption give flesh to incredible fantasies, and conspiracy theories among officials, peasants and brokers. At the same time she shows that in this labyrinthine world of bureaucratic obstacles and state control, local agrarian communities manage to find certain room for autonomy. Drawing on her extensive fieldwork in Mexico, and her experience in the field of development, Nuijten draws wide conclusions that can be applied to many societies. Providing a detailed ethnography, she focuses on various themes, including a theoretical anthropology of state power; families and factionalism after agrarian reform; local organisation; questions of law; corruption; and development theory. Focusing on the relationships between a local community and the state, this study is relevant not only to political anthropology, but also to development studies more generally.'an outstanding contribution' John Gledhill, Professor of Social Anthropology, University of Manchester, editor of the journal Critique of Anthropology.
Keywords: La Canoa (Jalisco, Mexico) -- Politics and government.; Ejidos -- Mexico -- La Canoa (Jalisco); Political anthropology -- Mexico.; Anthropologie politique -- Mexique.; POLITICAL SCIENCE -- Political Process -- General.; SOCIAL SCIENCE -- Anthropology -- Cultural.; Ejidos; Political anthropology; Politics and government; Mexico; Mexico -- La Canoa (Jalisco)